2020
DOI: 10.1057/s41291-020-00131-1
|View full text |Cite
|
Sign up to set email alerts
|

Female entrepreneurs’ gender roles, social capital and willingness to choose external financing

Abstract: From the perspective of gender roles, this study uses social capital as the intermediary variable to study female entrepreneurs’ willingness to choose external financing. We combine social and behavioral sciences and financing theory to explore interactions between gender roles, social capital, and willingness to choose external financing. We elaborate on the intermediary role of social capital between gender roles and external financing. We find differences in gender role types among female entrepreneurs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Sample of items that were deleted are: ''Not at all independent'', ''Women who are very assertive and independent don't have the concern about other people that most women have'', and ''I'd rather have a man as a boss at work than a woman.'' The exclusion procedure is consistent with a previous study by Wang et al (2020) that conducted the study within Chinese context. As the initial scales were developed within a Western context (Spence 1985;McCabe et al 2006), some of the items may not be relevant within Eastern context and hence, some adjustments were needed.…”
Section: Assessment Of Measurementsupporting
confidence: 59%
“…Sample of items that were deleted are: ''Not at all independent'', ''Women who are very assertive and independent don't have the concern about other people that most women have'', and ''I'd rather have a man as a boss at work than a woman.'' The exclusion procedure is consistent with a previous study by Wang et al (2020) that conducted the study within Chinese context. As the initial scales were developed within a Western context (Spence 1985;McCabe et al 2006), some of the items may not be relevant within Eastern context and hence, some adjustments were needed.…”
Section: Assessment Of Measurementsupporting
confidence: 59%
“…The role of external External support in the form of social interactionssocial relationships enhances women entrepreneurs' experiences. Social interactions reduce information asymmetries (Wang et al, 2020) and enhance women entrepreneurs' willingness to seek more external support and useful resources for business survival and growth (Leskinen, 2010). These external social relationships characterise the very nature of entrepreneurial networking for women (Aldrich et al, 1997;Aldrich and Zimmer, 1986;Starr and Yudkin, 1996) and can lead to innovative ideas and entrepreneurial solutions .…”
Section: Discussionmentioning
confidence: 99%
“…This creation of social relationships generates social capital that provides access to resources, e.g. finance, and reduces information gaps (Anderson and Jack, 2002;Wang et al, 2020). Underpinned by personal and emotional peerbased support, women entrepreneurs' external informal networks provide encouragement, learning and well-being (Brooks et al, 2018).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Other studies (e.g. Leitch et al, 2018;Wang et al, 2020) also confirmed the disadvantages of female entrepreneurs in seeking and obtaining external funding. Given the findings from these studies, it is difficult for female entrepreneurs to meet the development needs of their businesses and compete equally with their male counterparts.…”
Section: Female Entrepreneurs' Demand For and Supply Finance By Banks: A Mismatched Scenariomentioning
confidence: 71%
“…Many studies suggest that female entrepreneurs are discriminated against by banks because they lack collateral from ownership of property and banks are unwilling to accept household assets as collateral, they have an incomplete credit record and bank officials have little confidence in female entrepreneurs concerning their lower education attainment and training background (Isaga, 2019). In contrast, there are other scholars who have agreed that there is a lack of clear evidence of systematic gender discrimination in lending by financial institutions (Wang et al, 2020). However, many female entrepreneurs perceive or have witnessed this kind of discriminative treatment (Panda, 2018;Leitch et al, 2018;Isaga, 2019).…”
Section: Introductionmentioning
confidence: 99%